Evaluation of pulsed laser deposited SrNb0.1Co0.9O3−δ thin films as promising cathodes for intermediate-temperature solid oxide fuel cells - Chen, D.; Chen, C.; Gao, Y.; Zhang, Z.; Shao, Zongping; Ciucci, F. (Elsevier, 2015)
SrNb0.1Co0.9O3−δ (SNC) thin films prepared on single-crystal yttria-stabilized zirconia (YSZ) electrolytes are evaluated as promising cathodes for intermediate-temperature solid oxide fuel cells (IT-SOFCs). Geometrically well-defined polycrystalline SNC thin films with low surface roughness and high surface oxygen vacancy concentration are successfully fabricated by pulsed laser deposition. The thin films are characterized by basic techniques, e.g., X-ray diffraction for phase structure identification, scanning electron microscopy and atomic force microscopy for microstructures measurement, and X-ray photoelectron spectroscopy for elements quantification. Electrochemical impedance spectroscopy (EIS) is used to investigate oxygen reduction reaction activities of SNC thin films in symmetric electrochemical cells. Current collectors (Ag paste, Ag strip, and Au strip) are found to have negligible impact on polarization resistances. A slight decrease of the electrode polarization resistances is observed after adding a samarium doped ceria (SDC) buffer layer between SNC and YSZ. SNC thin-film electrodes exhibit low electrode polarization resistances, e.g., 0.237 Ω cm2 (SNC/SDC/YSZ/SDC/SNC) and 0.274 Ω cm2 (SNC/YSZ/SNC) at 700 °C and 0.21 atm, demonstrating the promise of SNC materials for IT-SOFCs. An oxygen reduction reaction mechanism of SNC thin films is also derived by analyzing EIS at temperature of 550–700 °C under oxygen partial pressure range of 0.04–1 atm.